Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae - Ribeiro-Júnior, Marco A.; Amaral, Silvana (Zootaxa, 2016)
We present distribution data of all Anguidae, Scincidae, and Teiidae lizards known from the Brazilian Amazonia, totaling 29 species-level taxa, belonging to 14 genera. This represents 11 more species-level taxa than previously reported for these families in this area. Data were based on literature and 46,806 specimens deposited in three North American and eight Brazilian museums, including the main collections harboring Amazonian material. Most species (~55%) are endemic to Amazonia. Except for Ameiva ameiva, that is present in several environments and domains, non-endemic species are either associated with open dry (semideciduous) forest or open vegetation (savanna) enclaves in Amazonia, occupying similar environments outside Amazonia, gallery forests within the Cerrado, or present disjunct populations in the Atlantic Forest. As a whole, six taxa are widespread in Amazonia, four are restricted to eastern Amazonia, four to western Amazonia, three to southwestern Amazonia, one to northern Amazonia, and seven to the southern peripheral portion of Amazonia. Besides, two species present apparently more restricted, unique distributions. Only three species have a distribution that is congruent with one of the areas of endemism (AE) recognized for other organisms (birds and primates), of which two occur in AE Guiana and one in AE Inambari.